PIWI-Interacting RNA-004800 Is Regulated by S1P Receptor Signaling Pathway to Keep Myeloma Cell Survival - Ma, Huanxin; Wang, Huihan; Tian, Fei; Zhong, Yuan; Liu, Zhuogang; Liao, Aijun (Frontiers in Oncology, 2020)
PIWI-interacting RNA (piRNA) is a kind of non-coding single stranded RNA which plays major roles in epigenetic expressions, genome rearrangement, and regulation of gene and protein. Because piRNAs are abnormally expressed in various cancers, they can be used as novel biomarkers and therapeutic targets. However, the roles of piRNAs in cancer cell growth and survival are not well known. Here, we are the first to provide evidence that PIWI-interacting RNA-004800 (piR-004800) is overexpressed in both exosomes from multiple myeloma (MM) patients’ bone marrow supernatant and primary MM cells. The expression level of piR-004800 is positively correlated with the stages of MM, according to the international staging system (ISS). In MM cell lines, downregulation of piR-004800 induced apoptosis and autophagic cell death. This was accompanied by in vitro and in vivo inhibition of cell proliferation. Our previous study shows that sphingosine-1-phosphate receptor (S1PR) signaling pathway plays a crucial part in MM cell proliferation. In this study, we find that S1PR signaling pathway can regulate the PI3K/Akt/mTOR pathway through control of piR-004800 expressions. Taken together our data supports an oncogenic role for piR-004800 in MM, which sheds insight into a new mechanism that may lead to therapeutic targets in MM, an incurable plasma cell neoplasm.